Perumusan Strategi Jasa Angkutan Penyeberangan PT ASDP Indonesia Ferry Lintas Bakauheni – Merak - Solihin Solihin; Muhamad Ferry Iqbal; Ricky Ricardianto (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The purpose of this research is to find out strengths and weaknesses (internal factors), threats and opportunities (external factors) and the strategy of the transport service company. PT. ASDP INDONESIA FERRY is a State-Owned Enterprise within the Ministry of Transportation which is authorized to carry out all activities in Ports of Bakauheni - Merak. SWOT Analysis was used as the analysis method. Based on the results, PT ASDP INDONESIA FERRY Bakauheni Branch, Bakauheni - Merak Route is in quadrant I with strength score of 3.82 and weakness score of 2.40. The difference between the two internal factors is 1.42. The score of opportunity value is 3.82 and the score of threat value is 2.80 that shows the difference between the two external factors is 1.02. These mean that the company is in a favorable position, which has positive strength and opportunities. Based on  the SWOT matrix, the S-O strategy is obtained, namely by utilizing strengths and making the most of opportunities.